ANALISIS EFISIENSI DAN EFEKTIVITAS PENGGUNAAN MODAL PADA LEMBAGA PERKREDITAN DESA (LPD) DESA PAKRAMAN SAPAT, TEGALLALANG, GIANYAR - Dewa Ayu Rumini; Ni Luh Ayu Teges Aryastuti (KRISNA: Kumpulan Riset Akuntansi, 2019)
The aims of this research was to find out the efficiency of capital use in the Village Credit Institution (LPD) of Pakraman Sapat Village, Tegallalang, Gianyar in terms of economic rentability and profitability of own capital from 2013-2017. To find out the effectiveness of capital use in the Village Credit Institution (LPD) of Pakraman Sapat Village, Tegallalang, Gianyar in terms of receivable turnover and working capital turnover from 2013-2017. The method used is quantitative analysis which includes Profitability Ratios, Activity Ratios, Statistical Analysis and qualitative analysis used to describe information so that it can support conclusions obtained from quantitative analysis. Based on the results of the analysis carried out, economic rentability achieved in 2013 was considered to be quite efficient, in 2014 it was considered very efficient, in 2015 and 2016 it was considered to be quite efficient, and in 2017 it was considered inefficient. The profitability of own capital achieved in 2013 was considered very efficient, in 2014, 2015 and 2016 were considered to be quite efficient and in 2017 it was considered less efficient. Accounts receivable turnover achieved in 2013 was considered very effective, in 2014, 2015, 2016 was considered quite effective and 2017 was considered less effective. The working capital turnover achieved in 2013, 2014, 2015, 2016 and 2017 is considered quite effective.